Perceptions of Collaborations: How Many Cooks Seem to Spoil the Broth?. Issue 2 (March 2020) - Maglio, Sam J.; Wong, Odelia; Rabaglia, Cristina D.; Polman, Evan; Reich, Taly; Huang, Julie Y.; Hershfield, Hal E.; Lane, Sean P.
Workers often work in groups of varying sizes, and those workers' work is often judged by others. To examine how the two might relate, we first asked respondents to report the optimal number of collaborators for a variety of different tasks, finding substantial variability across tasks (Supplementary Study) that tracked with perceived task complexity (Study 1). Accordingly, framing a given task as more complex made people want more collaborators collaborating on it (Study 2), and believing that a task had been performed by the right number of collaborators—neither too few nor too many—fostered more favorable evaluations of both simulated (Study 3) and real (Study 4) experience with the collaborative output. The results of this collaboration suggest that perceivers hold an optimal size in mind when thinking about collaborations and that collaborative work benefits from ostensibly hitting this mark.